The Value of Daytime Running Headlight Initiatives on Motorcycle Crashes in Malaysia. - Radin Sohadi, Radin Umar (2005)

(untitled)
Motorcycle casualties constitute more than two thirds or road accident victims in Malaysia and as high as 90 per cent in some Asian countries. One of the cost-effective interventions to address this problem is to encourage running headlight during the daytime. This paper presents the value of frontal conspicuity intervention as a low cost safety policy to reduce accidents involving motorcycle in Malaysia. Statistical and non-statistical analyses, the odds ratio, the time series analyses models and a simple graphical technique, were employed in this programme. Data were classified according to the daytime and night-time